Patients' Experiences of Life Challenges After Liver Transplantation: A Qualitative Study. (26th February 2021) - Taher, Mohammad; Toossi, Mohssen Nassiri; Jafarian, Ali; Rasti, Arezoo; Nayeri, Nahid Dehghan
Patients experience a new life with different challenges after liver transplantation (LT). Identifying these challenges can facilitate the improvement of their quality of life. This study aimed to explore patients' experiences of post-LT life challenges. This qualitative study was performed in 2019 through the content analysis approach. Participants were liver transplant recipients purposively recruited from a LT clinic. Semistructured interviews were conducted for data collection. Data were analyzed through Graneheim and Lundman's conventional content analysis approach. Meaning units were identified and coded, and the codes were grouped into subcategories and categories according to their similarities. In total, 18 transplant recipients were interviewed. Their age mean was 51 years and their transplant age ranged from 4 months to 12 years. Their post-LT life challenges were categorized into 4 main categories, that is, self-care deficit, the need for seeking information, fears and concerns, and hope–despair duality. Nurses and members of LT team are recommended to assess transplant recipients' life challenges and develop comprehensive plans for managing their challenges and problems and improving their quality of life.